Village Fund Allocation Management Accountability in Kebur Village, West Merapi District, Lahat Regency - Okta Via Andriani; Lukita Tripermata; Aris Munandar (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
This study aims to help solve the problems contained in the management of village fund allocations in Kebur Village. This research was conducted related to the accountability and development of village fund allocations in 2017-2019 in Kebur Village, West Merapi District, Lahat Regency. This research uses descriptive qualitative analysis method with data collection techniques used are observation, literature study, and documentation. The data analysis technique used in this study is to perform the data condensation process, data presentation, and conclusion. The results of this study indicate that the accountability and development of village fund allocations in 2017-2019 are quite good but not for each year because there are still many shortcomings in Kebur Village but technically and administratively are good, but still have to get guidance from the district government and district government.